Implementation of the education unit level curriculum (KTSP) and integrated science learning at SMPN 2 Barombong, Gowa Regency - Asrianti Kahar (Journal of Education Innovation and Curriculum Development, 2023)
The main problem is how to implement the Education Unit Level Curriculum (KTSP) and Integrated Science Learning at SMPN 2 Barombong, Gowa Regency. This problem is seen with a theological approach and discussed with qualitative methods and with content analysis (content analysis). In order to improve the quality of education, the curriculum is the main spearhead in achieving an increase in the quality of education. The current curriculum is the Education Unit Level Curriculum (KTSP) and Integrated Learning. Integrated learning as a concept can be said to be a teaching and learning approach that involves several related or integrated subjects both intra and between subjects to provide meaningful experiences to children. It is said to be meaningful because in integrated learning, Children will understand the concepts they learn through direct experience and connect them with other concepts they already understand so that they become a unified whole. The aim of this study was to get an overview of the implementation of the Education Unit Level Curriculum (KTSP), and to find out the difficulties of integrated science learning at SMPN 2 Barombong, Gowa Regency, and to provide solutions related to the difficulties faced by teachers in implementing integrated science learning at the school.